The Mediating Effect of Investment Decisions and Financing Decisions on The Effect of Corporate Risk and Dividend Policy against Corporate Value - EFNI, Yulia (Journal of Advanced Research in Law and Economics, 2017)
This study aims to determine the effect of mediation decisions on investment and financing decisions influence the company's risk and dividend policy on firm value. The unit of analysis in this research is company property and real estate sectors listed in Indonesia Stock Exchange continuously for 9 years (2001 – 2008) and has a complete financial report on the study period. This research study using descriptive analysis and inferensial to prove examine the relationship between the study variables with the five structural models using WarpPLS. This study is basically to analyze the patterns of relationships between variables in order to determine the effect of directly or indirectly, a set of independent variables (exogenous) to the dependent variable (endogenous). The company's risk and decision Invests able to increase the value of the company, while the dividend policy and funding decisions are not able to increase the value of the company.